Observation of the treatment and outcomes of patients receiving chemotherapy for advanced NSCLC in Europe (ACTION study) - Bischoff, Helge; van den Borne, Ben; Pimentel, Francisco L.; Arellano, Jorge; Langer, Frank; Leschinger, Monika I.; Thatcher, Nicholas (Current medical research and opinion, 2010)
Objective:The ACTION (Assessment of Cost and ouTcomes of chemotherapy In an Observational setting) study investigated associations between chemotherapy, patient/disease characteristics and outcomes in advanced non-small cell lung cancer (NSCLC) patients in clinical practice.Research design and methods:Chemonaïve NSCLC patients from five European countries were observed for 18 months from initiation of first-line chemotherapy; care was at the physician’s discretion.Main outcome measures:Survival and associated prognostic factors were estimated using Kaplan-Meier methods and a Cox proportional hazards model, respectively. Cluster analyses of baseline patient characteristics were also performed. Toxicity data were not considered in these analyses.Results:A total of 975 eligible patients with NSCLC (Stage IIIb/IV) were enrolled and provided baseline and response data; cluster analysis was performed on 829 patients and survival data were available from 906 patients. In first-line treatment, a 39.8% response rate, a 39.5% 1-year survival rate and unadjusted median survival of 9.3 months were observed. Prognostic factors for survival included performance status (PS), number of metastatic organs, gender and age. Five patient clusters were identified, highlighting patient heterogeneity in terms of baseline condition and age. PS was maintained or improved throughout first-line and second-line chemotherapy in half the patients receiving these treatments.Conclusions:ACTION provides valuable information about patient population, disease characteristics, treatment choices, prescribing patterns and outcomes in routine clinical practice in advanced NSCLC in Europe. Our findings suggest that maintenance of PS after first and subsequent lines of chemotherapy, and survival rates may both be higher than previously anticipated. Our results also showed an association between age and survival, which suggests that age should not exclude patients from receiving chemotherapy if they meet all other eligibility criteria.
Gesehen am 07.02.2023